Slip Effect on MHD Chemically Reacting Convictive Boundary Layer Flow with Heat Absorption - Mekonnen Shifferaw Ayano; Negussie Tadege Demeke (Journal of Engineering)
The aim of this paper is to investigate steady magneto micropolar fluid past a stretched semi-infinite vertical and permeable surface taking into account heat absorption, hall and ion-slip effect, first-order chemical reaction, and radiation effects. The system of coupled nonlinear equations is solved numerically and the effects of various parameters on the velocity, the microrotation, the temperature, and the concentration field are calculated. The following discovery was made: an increase in the hall parameter strongly enhances the fluid velocity, an increase in the heat absorption parameter increases the temperature, and an increase in the slip parameter decreases the velocity. Additionally, the local skin friction, Nusselt number, and Sherwood number are also analyzed for various parameters and presented in table form.